2016
DOI: 10.1016/j.athoracsur.2015.09.080
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Polyphenol Prevents Diabetic Rats From Acute Kidney Injury After Cardiopulmonary Bypass

Abstract: Preoperative oral administration of EGCG ameliorates AKI in a CPB model of diabetic rats through antioxidative properties. This simple method could be applied in a clinical setting as a prophylactic renal protection against AKI after CPB, especially for high-risk patients with diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 26 publications
1
21
1
Order By: Relevance
“…The mechanical-ventilation settings were similar to those in a previous study [8]; the only difference was the inspired gas. Because we used room air instead of higher inspired oxygen fraction as the inspired gas, the levels of blood gases (PaO 2 and PaCO 2 ) in our study were lower than those reported in previous studies [912]. However, the blood gas levels in the CA + ECLS and NC + ECLS groups did not exhibit any differences at the same time points in our study.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The mechanical-ventilation settings were similar to those in a previous study [8]; the only difference was the inspired gas. Because we used room air instead of higher inspired oxygen fraction as the inspired gas, the levels of blood gases (PaO 2 and PaCO 2 ) in our study were lower than those reported in previous studies [912]. However, the blood gas levels in the CA + ECLS and NC + ECLS groups did not exhibit any differences at the same time points in our study.…”
Section: Discussioncontrasting
confidence: 54%
“…Despite the decrease in hematocrit caused by hemodilution, sufficient oxygenation was maintained in both groups. Animal models have been reported to maintain adequate oxygen delivery to satisfy the whole body’s oxygen demands without blood product administration when the ventilator was supplied with higher inspired oxygen fraction [10, 12, 1618]. However, we ventilated only with room air even in the absence of a blood transfusion to maintain acceptable oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…CPB was performed using a surgical technique as previously described in our laboratory with some modifications (Video 1). 20,21 The right femoral artery was cannulated with a 24-gauge intravenous catheter (SURFLO ETFE I.V. Catheter; Terumo, Tokyo, Japan) to monitor systemic arterial pressure and to analyze arterial blood gas (epoc Blood Analysis System; Alere Medical Co, Tokyo, Japan).…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Our working group examined the influence of CPB and EGCG on hippocampi of piglets and we could show that pericellular edema, transcription factors like HIF1α or AIF, as well as cleaved caspase 3 were significantly attenuated in the EGCG group [91]. Also, other organs like kidney and lung profited from EGCG [97,98,99]. However, EGCG has not yet been tested in a clinical setting of CPB.…”
Section: Pharmacological Methods For Brain Protectionmentioning
confidence: 99%